2022
DOI: 10.1038/s41598-022-24236-z
|View full text |Cite
|
Sign up to set email alerts
|

Serial dependence in estimates of the monetary value of coins

Abstract: Perceptions of current stimuli are sometimes biased toward or away from past perceptions. This phenomenon is called serial dependence. However, it remains unclear whether serial dependence originates from lower-order perceptual processing, higher-order perceptual processing or cognitive processing. We examined the effects of serial dependence when participants estimated the total number of coins or the monetary value of coins displayed and found attractive effects in both tasks. The attractive effect observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…It has also been reported that feedback on task performance boosts serial dependence 27 . Serial dependence has also been confirmed for monetary values, which require high-level processing, such as calculation 17 . Taken together, these results suggest that both low-level visual processing (spatial localization) and high-level processing (abstract number) influence serial dependence effects in numerosity perception.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has also been reported that feedback on task performance boosts serial dependence 27 . Serial dependence has also been confirmed for monetary values, which require high-level processing, such as calculation 17 . Taken together, these results suggest that both low-level visual processing (spatial localization) and high-level processing (abstract number) influence serial dependence effects in numerosity perception.…”
Section: Introductionmentioning
confidence: 80%
“…The study of serial dependence has been conducted across diverse tasks that employ varying types of stimuli, including orientation perception 2 , 7 , 9 , numerosity perception 1 , 10 13 , motion perception 14 , face perception 15 , sense of agency 16 , and monetary values 17 . Attractive serial dependence is believed to stabilize the perception of continuously changing stimuli in the presence of noise, such as blinking or occlusion by objects 9 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of serial dependence has been conducted across diverse tasks that employ varying types of stimuli, including tilt perception 2,6,7 , numerosity perception 1,[8][9][10] , motion perception 11 , face perception 12 , sense of agency 13 , and monetary values 14 . Attractive serial dependence is believed to stabilize the perception of continuously changing stimuli in the presence of noise, such as blinking or occlusion by objects 6,15 .…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that feedback on task performance boosts serial dependence 20 . Serial dependence has also been con rmed for monetary values, which require high-level processing, such as calculation 14 . Taken together, these results suggest that both lowlevel visual processing (spatial localization) and high-level processing (abstract number) in uence serial dependence effects in numerosity perception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation